Morphological study of the hypoglossal and lingual nerves - Rie Shimotakahara; Hyeyong Lee; Daisaku Nishimoto; Shigemitsu Ogata (Wolters Kluwer Medknow Publications, 2016)
Background and objectives: In treatment of dental conditions and dental anaesthesiology, a thorough understanding of course, directions and distribution of nerves and blood vessels supplying the tongue is extremely important. However, the morphology of the nerves supplying the tongue has not yet been fully understood. We applied comparative anatomical approach in order to observe innervation of the tongue in detail, with the focus on the distribution of the lingual nerves and its communication with the hypoglossal nerve. Material and methods: Ten adult human tongues with no grossly detectable abnormalities that were resected from cadavers donated for anatomical study and five monkey tongues were used. Specimens were immersed in water and dissected under a stereomicroscope, and gross examination of the morphology and directions of branches of the hypoglossal and lingual nerves,communicating branches between these two nerves, and their connection status was done. Observations: All branches shared common morphological characteristics: branches near the root of the tongue were relatively straight, while they meandered and formed loops nearer to the apex of tongue. In addition to the branch on the anterior muscle bundle of the hyoglossus muscle, which could be easily observed,there were two more communicating points (total of three communicating branches in both humans and Japanese macaques: in the inner part of the genioglossus muscle and the apex of the tongue). Conclusions: The levels of communicating nerve complexity between the hypoglossal nerve and the lingual nerve and the thickness of nerve fibers varied among individual subjects, but there was a common three-site communication pattern.